Supplements for yearling steers on bluestem pastures during the latter part of the grazing season. - Smith, E.F.; Baker, F.H.; Walker, G.L. (Kansas Agricultural Experiment Station, 2011)
The nutritive value of bluestem pasture usually declines rapidly after mid-summer. This test is an attempt to find ways to economically increase the rate of gain after mid-summer with small quantities of concentrate feed.
Keywords: Beef; Steers; Gain; Concentrate feed